The role of digital technology in scaling social impact in South Africa - Hutiri, Neo (Graduate School of Business (GSB), 2025)
Social entrepreneurship is an important contributor to South Africa's business environment and social fabric, however scaling social impact continues to be a challenge. To date, very limited studies have considered scaling strategies that social enterprises in South Africa use to grow their impact. In particular, no academic work has been done on how digital technology impacts on these scaling strategies. This thesis uses a descriptive case study method to examine scaling strategies of 21 social enterprises and the role of digital technology on their strategies. The key findings of this research have been summarised into top ten key learnings that can help and guide social enterprises building scaling strategies for social impact in South Africa.